Integrated Dynamic Vehicle and Crew Scheduling Using Multi-Agent System - Shibghatullah, Abdul Samad; Selamat, Mohamad Hisyam; Abdullah, Nazri (2005)
Vehicle and crew scheduling problem is remarkably difﬁcult to solve because of the large number of resources that need to be allocated, very complex rules for the allocation of crew shifts, high cost of overtime and unpredictability of the urban trafﬁc and crew availability. This article proposes a Multi-Agent System (ll/MS) approach to solve integrated dynamic vehicle and crew scheduling problems. MAS are capable of real-time scheduling and dynamic re-scheduling whenever unpredictable events and change of resources or demands occurs. This paper proposes a conceptual framework for an integrated and dynamic vehicle and crew scheduling by using the concept of MAS.